Larvicidal, Repellent, and Irritant Potential of the Seed-Derived Essential oil of Apium graveolens Against Dengue Vector, Aedes aegypti L. (Diptera: Culicidae) - Kumar, Sarita; Mishra, Monika; Wahab, Naim; Warikoo, Radhika (Frontiers in Public Health, 2014)
Aedes aegypti L. is one of the primary disease vectors spreading various dreadful diseases throughout the world, specifically over tropics and subtropics. Keeping in view the adverse effects of chemical insecticides-based intervention measures, the eco-friendly and bio-degradable essential oil extracted from the seeds of celery, Apium graveolens were investigated for its efficacy against Ae. aegypti. Larvicidal bioassay carried out with the seed oil against early fourth instars of Ae. aegypti caused an LC50 and LC90 values of 16.10 and 29.08 ppm, respectively, after an exposure to 24 h. The cidal effect of the celery seed oil augmented by 1.2-fold; after an exposure to 48 h; revealing an LC50 value of 13.22 ppm. Interestingly, the seed oil did not cause immediate larval mortality, suggesting a delayed toxicity against the larval stage. Present investigations also revealed remarkable effective repellency of the oil leading to 100% protection till 165 min as compared to control that did not result in any repellency against adult Ae. aegypti. Interestingly, only one bite was recorded in the 165th-min after which only two bites were scored until 180 min of exposure of the adult mosquitoes to the oil. An exciting observation was that the knocked-down effect in adults exposed to 10% oil-impregnated papers. The contact irritancy assays with paper impregnated with 1% celery seed oil caused first flight only after 4 s resulting in an average of 63.66 flights during 15 min of exposure revealing the relative irritability of 26.97. The qualitative phytochemical analysis of the seed oil showed the presence of flavonoids, lactones, and terpenoids as the major constituents suggesting their probable role in the toxicity. Our results confirmed that celery seed essential oil can be used as an efficient larvicide and repellent against Ae. aegypti. The identification of the bioactive components, their mode of action, and studying effects on non-target organisms and the environment would help in devising mosquito-management strategies.